Comparison of the Efficacy (In Terms of No Pain) of Continuous and Interrupted Suturing in Episiotomy Repair - Qurat-Ul-Ain, Samina Ather, Hafiza Mehreen Gul (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy (in terms of no pain) of continuous and interrupted suturing in episiotomy repair. Materials & Methods: This randomized controlled trial was done at department of Obstetrics & Gynaecology, Civil Hospital, Bahawalpur during a period of six months from 7th November 2019 to 6th May 2020. Women with singleton pregnancy women who underwent episiotomy to facilitate the delivery of the head in the labour room, 20 to 40 years of age were included. Group 1 included the women in which continuous suturing was done while group 2 included the cases in which interrupted suturing was done. In both groups, episiotomy repair was done by the researcher herself. All patients were advised Tab. Diclofenac sodium 50mg 1xBD post-operatively and efficacy was noted after 48 hours by VAS scale. Results: The mean age of women in group 2 was 27.48 ± 3.59 years and in group 1 was 27.36 ± 3.52 years. Majority of the patients 75 (75.0%) were between 20 and 30 years of age. The mean gestational age of group 2 was 39.48 ± 1.27 weeks and in group 1 was 39.38 ± 1.28 weeks. Efficacy (in terms of no pain) was seen in 18 (36.0%) patients in Group 2 (interrupted group) while in Group 1 (continuous), it was seen in 36 (72.0%) patients with p-value of 0.0001. Conclusion: continuous suturing of episiotomy repair was observed to be the most effective in terms of significant less post-operative pain compared to interrupted suturing.